Obstetric Risk Factors and Anal Incontinence among Women with Previous History of Vaginal Delivery - Azizah Nurdin; Trika Irianta; Mardiah Tahir; Maisuri T. Chalid (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To investigate the obstetric risk factors of the anal incontinence in mothers with previous history of vaginal delivery. Methods: The was a case-control study conducted in the Obstetrics and Gynecology Department of Dr.Wahidin Sudirohusodo Hospital, Faculty of Medicine, Universitas Hasanuddin, Makassar, during the period of February 2015 through January 2016. The research instruments were used to evaluate obstetric risk factors and the anal incontinence was the self-administered questionnaire and Fecal Incontinence Severity Index. The data were analyzed statistically using the Chi-square test with the significant value of p<0.05. Results: A total of 300 subjects were recruited in this study. The research results indicated that the parity of ï,³ 3, the assisted vaginal delivery history (vacuum extraction), and the prolong second stage of labor had a significant correlation with the anal incontinence with p value=0.026, OR (95% CI) = 1.8 (1.07-3.03), p=0.018 with OR (95% CI) =3.65 (1.2-10.7) and p=0.006 with OR (95% CI) = 2.9 (1.2-6.7).The history of episiotomy and the delivery of the baby ï,³ 4000 gram had no correlation with the anal incontinence. Conclusion: Parity, vacuum delivery and prolong second stage of labor have an association with anal incontinence among women who has history of vaginal delivery. Keywords: anal incontinence, obstetric risk factors, vaginal delivery